TERJADIKAH UNDERPRICING HARGA PENAWARAN UMUM PERDANA SAHAM? (Studi atas Harga Penawaran Umum Perdana Saham PT Krakatau Steel) - Prasetyo, Whedy (Universitas Jember, 2011)
Initial Public Offering PT. Krakatau Steel(KARS) stock prices at government decision for Initial Public Offering determine to price under boundary Rp. 850,00per stock stringindicationinformationconfer underpricing, at matter with three indication. This paper is explane at underpricing phenomenon Initial Public Offering, and Initial Public Offering process to PT. Krakatau Steel, with support for research Rock (1986) and, Ritter and Welch (2002). The process writing objective paper is idea suggest at prices determine per stock principal be based on study at PT. Krakatau SteelInitial Public Offering prices should didnât based for number calculate, however moment for intangible advantage calculate. Finally this paper to answer the question what the Initial Public Offering underpricing stock prices can be happened? Keywords: Initial Public Offering (IPO), and underpricing.